Evaluation of serum vitamin D levels in premenopausal women with iron deficiency anemia - Atalay, Eray; Bilgehan, Gökhan; Şişman, Pınar; Erdoğdu, Halil İbrahim (The European Research Journal, 2020)
Objectives: In recent years, many effects of vitamin D except on bone metabolism have been discovered. Vitamin D contributes to the correction of the anemia by acting on the erythroid precursors in the bone marrow via Vitamin D Receptor and provides the elimination of free radicals and prooxidant substances secondary to iron deficiency due to its antioxidant effect in iron deficiency anemia (IDA). Methods: A total of 97 female premenopausal women aged 18-44 were included in the study. Fifty patients with hemoglobin levels below 12 mg/dl and iron deficiency were classified as IDA group, and 47 subjects with hemoglobin levels of 12 mg/dl and above were classified as control group. The demographic data and biochemical parameters of all patients included in the study were analyzed. Results: The vitamin D of the patient group was found to be 7.87 ± 3.63 ng/ml and the vitamin D of the control group was 11.84 ± 6.72 ng/ml. The difference between the groups was statistically significant. There was a positive correlation between serum vitamin D and serum hemoglobin, hematocrit, serum MCH, serum iron level, transferrin saturation index, ferritin. Conclusions: In the light of the results of our study and other studies in the literature, we think that vitamin D deficiency may be important in patients with IDA and that vitamin D deficiency in these individuals will contribute to the regulation of anemia due to positive effects of vitamin D on both erythropoiesis and hepcidin in IDA are considered. However, larger studies are needed to clarify this issue.